Simulation study of an adaptive phase alignment system for optical heterodyne communications under misalignment conditions. - Patel, K.
A postphotodetection adaptive phase alignment system using an aperture array of photodetectors is presented to reduce the signal loss in an optical (free-space) heterodyne receiver resulting from wavefront misalignment (tilt) on a satellite platform. This paper compares two kinds of rectangular aperture configurations-full aperture and array aperture configurations-via a software simulation study of the error performance after DPSK demodulation for different angles of arrival (tilt) of the received signal wavefront. For the array configuration, an adaptive phase alignment system is used that phase aligns the signals from the different photodetector array elements, and constructively adds them to yield a higher signal magnitude as compared to that of signal of a single-element photodetector of the same total area. The optimum aperture length for a given wavefront misalignment is derived, and is verified via simulation
Keywords: DPSK demodulation; Angles of arrival; Aperture array; Array aperture; Error performance; Free-space receiver; Full aperture; Misalignment conditions; Optical heterodyne communications; Optical heterodyne receiver; Optical satellite links; Optimum aperture length; Photodetectors; Postphotodetection adaptive phase alignment system; Received signal wavefront; Rectangular aperture configurations; Satellite platform; Signal loss reduction; Signal magnitude; Simulation study; Software simulation; Tilt; Wavefront misalignment